Global Women's Issues Women in the World Today, extended version - Aragon, Janni; Miller, Mariel (Open textbook library., 2012)
We cannot solve global challenges unless women participate fully in efforts to find solutions. Female participation in the private sector is a crucial economic driver for societies worldwide. Economic security benefits every facet of a woman's life, with positive effects on the health, education and vitality of families. Learn about women who are changing their societies for the better. This book is based on the twelve critical areas of concern identified in the Beijing Declaration and Platform for Action at the Fourth World Conference on Women in Beijing in 1995: The burden of poverty on women, unequal access to education and training, inequalities and inadequacies in and unequal access to health care and related services, violence against women, the effects of armed or other kinds of conflict on women, including those living under foreign occupation, inequality in economic structures and policies, inequality between men and women in the sharing of power and decision-making at all levels, insufficient mechanisms at all levels to promote the advancement of women, lack of respect for and inadequate promotion and protection of the human rights of women, stereotyping of women and inequality in women's access to and participation in all communication systems, especially in the media, gender inequalities in the management of natural resources and in the safeguarding of the environment, and persistent discrimination against and violation of the rights of the girl child. This extended version of Global Women's Issues: Women in the World Today includes, for each chapter, a summary, key words, multiple choice questions, discussion questions, essay questions, and a list of additional resources. Copies of the original book are also available in Arabic, Portuguese, and Spanish.